Identification of Ferroptosis-Related Genes in MAFLD/MASH and HQHF Validation [Corrigendum] - Liu S; Zhang L; Xu J; Zhao Q; Shang D; Liu X; Zhang Q; Liu M; Zhao W (Hepatic Medicine: Evidence and Research)
Liu S, Zhang L, Xu J, et al. Hepat Med. 2025;17:13–24. The authors have advised that there are errors in the last sentence of the Results section in the Abstract on page 13. The text “We verified the reliable genes with diagnostic value through qPCR, and the results suggested that HQHF can lower the transcription levels of P4HA1, NR4A1, and EFEMP1, while increasing the transcription levels of ENo3, GRIA3, ME1, and FADS2, confirming our ROC results” should read “We verified the reliable genes with diagnostic value through qPCR, and the results suggested that HQHF can increase the transcription levels of P4HA1, NR4A1, and EFEMP1, while lowering the transcription levels of ENo3, GRIA3, ME1, and FADS2, confirming our ROC results”. The authors apologize for the errors.